Improved Salt Tolerance and Metabolomics Analysis of Synechococcus elongatus UTEX 2973 by Overexpressing Mrp Antiporters - Cui, Jinyu; Sun, Tao; Li, Shubin; Xie, Yaru; Song, Xinyu; Wang, Fangzhong; Chen, Lei; Zhang, Weiwen (Frontiers in Bioengineering and Biotechnology, 2020)
The fast-growing cyanobacterium Synechococcus elongatus UTEX 2973 (Syn2973) is a promising candidate for photosynthetic microbial factory. Seawater utilization is necessary for large-scale cultivation of Syn2973 in the future. However, Syn2973 is sensitive to salt stress, making it necessary to improve its salt tolerance. In this study, 21 exogenous transporters plus F1F0-type ATPase were individually overexpressed in Syn2973 to evaluate their effects on salt tolerance. The results showed that the overexpression of three Mrp antiporters and the F1F0-type ATPase significantly improved the salt tolerance of Syn2973. Notably, overexpressing the Mrp antiporter from Synechococcus sp. PCC 7002 improved cell growth by 57.7% under 0.4 M NaCl condition. In addition, the metabolomics and biomass composition analyses revealed the possible mechanisms against salt stress in both Syn2973 and the genetically engineered strain. The study provides important engineering strategies to improve salt tolerance of Syn2973 and is valuable for understanding mechanisms of salt tolerance in cyanobacteria.